Tough Responsive Polymer Hydrogels and Devices Crosslinked by Block Copolymer Micelles. Issue 1 (7th June 2019) - Fu, Jun
Abstract : Amphiphilic block copolymer Pluronic F127 is modified by acrylate groups on both ends, generating a functional triblock copolymer F127DA. The functional copolymer forms micelles in aqueous solution, with the hydrophilic PEO coronae containing reactive double bonds. The F127DA micelles are copolymerized with acrylamide, 2‐acrylamido‐2‐methylpropane sulfonic acid (AMPS), and methyl chloride quaternized N, N ‐dimethylamino ethylacrylate (DMAEA‐Q) through free radical copolymerization, generating hydrogels with outstanding toughness, fatigue resistance, and responsiveness to pH, ion strength, and electric field. The polyelectrolyte hydrogels are assembled through electrostatic interactions into devices with periodic structures and property contrast, which enables shape transformations upon external stimuli.